INFLUENCE OF REPEATED MIDDLE EAR INFECTIONS AND CONDUCTIVE HEARING LOSS IN THE PRESCHOOL PERIOD ON PHONOLOGICAL AWARENESS OF FIVE-YEAR-OLD CHILDREN - Katja Globevnik (The Society for Children with Metabolic Disorders, 2022)
Introduction: Recurrent otitis media and conductive hearing loss in the early preschool period often cause fluctuating hearing condition that significantly affects a child's appropriate speech and language development. The possibility of phonological disturbances is increased. Material, subjects and methods: The examined children comprised 206 children aged between 4.04 and 5.06 years, who participated in the speech and language screening test at the age of five years in Health Centres in north-eastern Slovenia from March to August 2021. Results: The incidence of otitis media in children is 55%. Problems in phonology, language problems, and problems in pragmatics have been shown to be the most common consequences of otitis media. Conclusions: Multiple prolonged episodes of otitis media can cause hearing fluctuations or conductive hearing loss, which causes speech and language problems.